Structural analysis as a tool for the elaboration of socio-cultural diagnosis located - Fernández, Federico; Matías Peralta, Sebastián; Arrueta, Patricia Marisel (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
This work was based on a research project whose general objective was the development of a diagnostic referential model created from the construction of a mixed database. Our starting point was bases on a structural analysis of a historical and situated nature, which has enabled us to recognize central elements that allow a more precise planning of the socio-cultural consequences of actions to be developed in the field by private or state agencies; taking into account, above all, the conditions of precariousness and marginality in which the populations analyzed here find themselves.